Valuation and reporting of intangibles – state of the art in 2004. (20th April 2005) - Roos, Goran; Pike, Stephen; Fernstrom, Lisa
For 500 years, companies have been obliged to report their operations and success, or lack of it, to their stakeholders. Traditionally, this function has been performed by conventional accounting methods. However the recent corporate collapses have shown us that traditional financial accounting methods do not always work. Indeed, there has been a growing demand in the last decade for organisations to report on the intangible resources they deploy in their operations to give a more balanced view of their output. The objective of this paper is to look at how intangible resources maybe measured, valued, and disclosed meaningfully to organisational stakeholders in an effort to secure sustainable advantage over competitors or levels of performance that exceed social and economic budgetary expectation.